Efektivitas Kinerja Pada Bidang Pencegahan dan Penanganan Kekerasan Terhadap Perempuan dan Anak Dinas Pemberdayaan Perempuan dan Perlindungan Anak Kota Bekasi - Toto Prasetyo; Evi Priyanti; Dadan Kurniansyah (Jurnal Ilmiah Wahana Pendidikan, 2022)
The concept of effectiveness is defined differently by experts, because it is in accordance with the basic knowledge possessed, even though it is different, but the ultimate goal of the concept of effectiveness is the goal that is carried out correctly according to what has been planned. Performance is a result that can be achieved by a person within a certain period of time in accordance with the ties that lead to an organizational goal. Performance measurement must consider quantity, quality, and timeliness. This study uses a qualitative research method with a descriptive approach. The performance of the Division of Prevention and Handling of Violence Against Women and Children of the Bekasi City Women's and Children's Empowerment Service is very good